2012
DOI: 10.1016/j.jpain.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Central Pain Processing in Shoulder Pain: Converging Results From 2 Musculoskeletal Pain Models

Abstract: Recent reports suggest deficits in conditioned pain modulation (CPM) and enhanced suprathreshold heat pain response (SHPR) potentially play a role in the development of chronic pain. The purpose of this study was to investigate whether central pain processing was altered in 2 musculoskeletal shoulder pain models. The goals of this study were to determine whether central pain processing: 1) differs between healthy subjects and patients with clinical shoulder pain, 2) changes with induction of exercise induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 36 publications
11
65
0
Order By: Relevance
“…In that study, patients who showed reductions in TSS after surgery experienced clinically meaningful improvements in shoulder pain at three months post-intervention. In contrast those patients in whom there was no change in TSS after surgery continued to report pain and interference in daily activity at three months [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, patients who showed reductions in TSS after surgery experienced clinically meaningful improvements in shoulder pain at three months post-intervention. In contrast those patients in whom there was no change in TSS after surgery continued to report pain and interference in daily activity at three months [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The observed reductions in TSS after body-based interventions are therefore hypothesized to indicate changes that would be favorable for clinical outcome. Recent work supporting this theory indicates available plasticity within the nervous system (reductions in TSS after an intervention) to be prognostic of recovery from shoulder pain [24]. …”
Section: Introductionmentioning
confidence: 99%
“…20,21,36,37,53,61 Central sensitization has been linked to the progression and maintenance of chronic pain, and disrupting this process is paramount. 2,34 Thus, the changes in pain sensitivity that accompany shoulder pain provide a therapeutic target for manual therapy and a potential mechanism for its beneficial clinical effects.…”
mentioning
confidence: 99%
“…These measures were selected because we expected them to be responsive to the combined personalized intervention and associated with pain relief. For example, elevated suprathreshold heat pain responses normalized post-operatively in the clinical cohort [93] and its changes were associated with improvements in post-operative shoulder pain and disability [96]. …”
Section: Methodsmentioning
confidence: 99%